(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The focus of this paper (study) is to investigate the cracking of concrete bridge decks and the sealants used in repairing transverse cracks. Cracking could occur in both hardened mature concrete, early age concrete. Several factors affect concrete cracking, such as age-dependent material properties, thermal, moisture-related stresses and strains, material viscoelastic behavior, restraints, concrete expansion and contraction, casting sequence, formwork, material characteristics, and environmental exposure. The causes of early age cracking primarily attributed effects such as plastic shrinkage, temperature effects, drying shrinkage and autogenously shrinkage. This deck cracking could greatly reduce durability, lead to loss of functionality, loss of stiffness, and ultimately the loss of structural safety.